Chitosan membrane filtering characteristics modification by N-ion beams - Pikul Wanichapichart (2018)
Chitosan is a fascinating material involving many important applications in various fields. Chitosan membranes developed for solution filtering have been for the first time modified by nitrogen ion beams for improving filtering characteristics. This study shows that although glutaraldehyde, as a cross-linking organic substance, can increase positive fixed charges of chitosan membranes, the charges can be further increased by ion implantation. After bombardment with low-energy (15-30 keV) nitrogen ions, there was a tendency for the membrane hydraulic conductivity to increase as the ion dose increased from 1.5 × 1014to 3.0 × 1014 ions/cm2and, consequently, a slight decrease in membrane impedance was observed. Further decrease of the impedance was evidenced if the membrane was bathed in a higher salt concentration. In addition, membranes with smaller impedance possessed greater conductance and capacitance. After being implanted with N ions to doses between 1.5 × 1014and 14 × 1014 ions/cm2, the membranes exhibited greater diffusion potential drop in salt concentration gradient, implying a better separation between anionic and cationic salt species. The N ions increased the membrane permeability ratio of Cl-to K+by 3 times. These results implied that ion implantation at low energies improved the membrane ionic charges for separation work. © 2007 Elsevier B.V. All rights reserved.